My body, myself. (Sydney Encyclopaedia Britannica Australia, 2001)
"Discover how and why your body works, stimulating projects and meaningful activities, experience virtual reality and 3D models, full screen video and images with zoom function."
System requirements: Operating System Windows 98/Me/2000/XP, Pentium III with 450 MHz processor or faster hard drive space: 130 MB, 64MB (128MB Win2000, XP), AGP 3D Graphics card with 4 MB (8MB recommended) running at 800 x 600 16 bit colour, CD-Rom speed 8x or faster, any 16 bit soundblaster or 100% compatible.
Keywords: Body, Human; Human growth; Human anatomy; Human physiology